Evaluation of Immediate and Delayed Placement of Post on Sealing Ability of Periapical Area: An Original Research - Pramod Punchiri Sadan; Smita Durga Dutta (Wolters Kluwer Medknow Publications, 2024)
Objective: The purpose of this research is to compare the effects of post placement-immediate and delayed-on the periapical area's capacity to close after root canal therapy. Techniques: A random split of 60 recently removed human single-rooted teeth were made into two groups: Group A received immediate post placement, whereas Group B received post placement after seven days. Standard guidelines were followed in the preparation of root canals and the placement of posts. A dye penetration method was used to measure microleakage, a measure of sealing capacity. Findings: Compared to the immediate post-placement group (0.62 ± 0.08) (P < 0.001), the delayed post-placement group had a considerably lower mean microleakage score (0.35 ± 0.06), showing improved sealing capacity. In conclusion, post implantation done later enhances the periapical area's sealing capacity after root canal therapy. This research underscores the significance of scheduling endodontic treatments to maximize treatment success and improve tooth retention, as well as the possible therapeutic advantages of postponing post implantation.